Direction of Nigerian Newspaper Rejoinders (Nordic Journal of African Studies, 2004)
This paper examined rejoinders by corporate bodies and public figures to news stories and editorials in two Nigerian newspapers from 1999-2001 with a view to determining which type of rejoinders - mild or adversarial - were favoured. The findings of the paper clearly indicates that majority of rejoinders were adversarial containing abusive language directed at journalists and media organizations. The paper takes the position that these rejoinders point to the scant regard in which the Nigerian print media is held and recommends that the cherished value of balance in helping to reverse this worrisome trend.